1997
DOI: 10.1016/s0015-0282(97)81858-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sequential three-monthly hormone replacement therapy on several cardiovascular risk estimators in postmenopausal women

Abstract: Objective: To investigate the changes in plasma lipids and lipoproteins, low-density lipopro tein (LDL) oxidizability, and plasma homocysteine during postmenopausal sequential 3-monthly hormone replacement therapy.Design: Open longitudinal prospective study. Setting: Gynecological outpatient departm ent of a university hospital. P atient(s): Thirty-nine healthy nonhysterectomized postmenopausal women.In terv en tion (s): Oral conjugated estrogen, 0.625 mg/d, combined with oral medrogestone 10 mg/d during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 24 publications
2
17
2
Order By: Relevance
“…The novelty of our study compared to previous ones is the study cohort comprising patients with high cardiovascular risk since they had angiographically verified CAD, and the use of transdermal application of 17β-estradiol as HRT. Our results are in contrast to some earlier reports [9, 10, 11, 12, 13]that claim that HRT favorably modulates homocysteine, with the most marked reduction occurring in those with the highest concentrations. Walsh et al [9]found an absolute decrease of 7% in plasma homocysteine in healthy women on conjugated equine estrogen and continuous MPA, i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The novelty of our study compared to previous ones is the study cohort comprising patients with high cardiovascular risk since they had angiographically verified CAD, and the use of transdermal application of 17β-estradiol as HRT. Our results are in contrast to some earlier reports [9, 10, 11, 12, 13]that claim that HRT favorably modulates homocysteine, with the most marked reduction occurring in those with the highest concentrations. Walsh et al [9]found an absolute decrease of 7% in plasma homocysteine in healthy women on conjugated equine estrogen and continuous MPA, i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Although early reports consistently showed a moderate decrease in plasma homocysteine on HRT [9, 10, 11, 12, 13], more recent studies have either failed to observe such an effect or merely observed a transient decrease in homocysteine levels [10, 14, 15]. The investigations have been done in healthy postmenopausal women free of CAD, and a variety of HRT formulations have been used, including conjugated equine estrogens [10, 13], which is a less frequently used HRT regimen in Europe compared to the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influence of oestrogens on the methionine/ homocysteine metabolism is further refuted by the absence of a long-term effect of hormone replacement therapy on the level of plasma homocysteine. 40 Since the level of plasma folate is a critical modulator of the MTHFR mutation, differences in the level of plasma folate between men and women may also have contributed to the gender-dependent association. A previous study in elderly subjects, however, reported no difference in the level of plasma folate between men and women despite the higher folate intake of women.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of gonadal steroids on homocysteine metabolism are not exactly clear. Studies are available suggesting that plasma homocysteine levels increase with natural menopause [16] and HRT in postmenopausal women and rats with surgical menopause decreases homocysteine levels by affecting homocysteine metabolism nongenetically [17][18][19]. But this effect of HRT on homocysteine levels is not always compatible with the clinical end result.…”
Section: Discussionmentioning
confidence: 99%